ANALISA STANDARISASI MUSEUM BATIK DENGAN PENDEKATAN KEARIFAN LOKAL BUDAYA ARSITEKTUR SURAKARTA - Maysitha Fitri Az Zahra; Ully Irma Maulina Hanafiah; Febri Toni Setiawan (LPPM Institut Desain dan Bisnis Bali, 2021)
Batik, which is rich in symbols and philosophies for the Indonesian people, has now been recognized by UNESCO as a Representative List of the Intangible Cultural Heritage of Humanity. The beginning of the emergence of batik in Indonesia is in the city of Solo, and comes from the Pajang kingdom 400 years ago. With the passage of time, batik continues to grow and produces various variations and innovations, from raw materials to the drawn motifs. However, it is very unfortunate that not all of the previous heritage batik can be maintained. Recently, there has been a batik museum created by individuals or institutions, but in the design, some interior elements are less than optimal in their arrangement. So they don't affect the batik stored or on display. In this research, focus of the discussion is on standardization which discusses spatial planning, facilities, collections, lighting, ventilation, acoustics and museum security, which are combined with local wisdom of Surakarta architecture, so that the data becomes a batik museum with character and can preserve the stored batik. This research uses a case study of the Surakarta batik museum, and the final results of this study can be used as a guide for designing a museum with fabric materials in it.